Quality of Service in Improving Customer Satisfaction at MSMEs in Purbalingga - Aspizain Caniago; Agung Edi Rustanto (Budapest International Research and Critics University, 2022)
In the business world, fulfilling the needs and desires of consumers is one of the tasks that must be fulfilled by business people. Increasingly tighter competition makes business people prioritize customer satisfaction. The purpose of this research activity is to determine the effect of service quality on customer satisfaction at the Central Motor Workshop. The population of this study is unlimited and the sample of 96 respondents is known by using the lameshow formula. This type of research uses a quantitative approach, with data collection techniques using questionnaires. In this study the research tests used were validity, reliability, correlation analysis, descriptive analysis, simple linear regression, t-test and the coefficient of determination. In this study using a simple regression correlation coefficient. The effect of service quality (X) on customer satisfaction (Y), based on the results of the T-test in this study, the test results show that the independent variable, namely service quality, has a positive and significant effect on smooth production. Significant at the 0.000 level, because 0.000 <0.05, it is concluded that Ho is rejected and Ha is accepted. Thus it can be stated that the service quality hypothesis has a significant effect on customer satisfaction. From the t value indicates that service quality has a positive and significant effect on customer satisfaction. The results of this study indicate that service quality has a significant effect on customer satisfaction